2017
DOI: 10.4236/abcr.2017.61002
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Performance of Breast Cancer Screening (Breast Self-Examination, Clinical Breast Exam and Mammography)

Abstract: Background: Breast cancer is the most common malignancy among women in Saudi Arabia. Despite the availability of early detection methods to diagnose breast cancer, a huge number of women are still unaware about these methods. This study was conducted to identify the attitude of women in Medina toward breast cancer screening methods, including breast self-examination (BSE), clinical breast examination (CBE) and mammography. Methods and Materials: A cross-sectional survey has been conducted on 124 women aged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In any case, the literature indicates a family history of BC in any first-degree relative is known to increase a women risk of disease onset [32] [33] [34] [35]. In addition, these results are consistent with the work of Buxton et al, [36], Caruso et al, [37], Silk et al, [38], Aljohani et al, [39], and a meta-analytic review by Katapodi et al, [40] all of whom found an association between risk perception and family history of breast cancer. In developed countries, about twenty-five percent of inter-individual differences mainly due to genetic causes of BC [41].…”
Section: Discussionsupporting
confidence: 86%
“…In any case, the literature indicates a family history of BC in any first-degree relative is known to increase a women risk of disease onset [32] [33] [34] [35]. In addition, these results are consistent with the work of Buxton et al, [36], Caruso et al, [37], Silk et al, [38], Aljohani et al, [39], and a meta-analytic review by Katapodi et al, [40] all of whom found an association between risk perception and family history of breast cancer. In developed countries, about twenty-five percent of inter-individual differences mainly due to genetic causes of BC [41].…”
Section: Discussionsupporting
confidence: 86%
“…Several other researchers also reported similar results. For examples, Aljohani et al reported that 35.5% of their study patients had ever performed BSE, and 27.3% performed BSE monthly 11 ; Obaiko et al reported 30% of ever BSE practice and 14% of frequent BSE 8 ; Aker et al even reported a lower prevalence of regular BSE practice (12.6%). 14 In contrast, in the study of Deniz et al, 51% of study patients have performed BSE.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 These results are similar to some other studies conducted in Nigeria, 7 Sahara region, 8 Iran, 9 Kuwait, 10 and Saudi Arabia. 11 There are a number of factors that may influence the knowledge and practice of BSE in women, such as literacy, 11,12 occupation, 13 family history of BC, 14,15 marital status, 12 and access to BSE information. 16…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Alsaraireh and Darawad (2018), who were mainly interested in questioning BC screening program participation, reported that the minority of the participants had engaged in such a program. At a cancer screening center in Medina, a broader perspective was adopted by Aljohani et al (2016), who highlighted the low level of utilization by Saudi women and argued that only 35.5% of attended women had practiced BSE.…”
Section: Discussionmentioning
confidence: 99%